Gender Differences in Vocational Interest of Elementary School Children in India - Sanwal, Suniti (JOURNAL OF INDIAN EDUCATION, 2021)
An interest inventory was developed to identify the vocational interests of elementary stage students. The inventory was developed across 14 vocational areas, which were identified as high growth sectors for employment and on which vocational courses were being offered from Class IX onwards under National Skills Qualification Framework (NSQF). The inventory was administered to 1700 students of Classes VII and VIII in the states of West Bengal, Telangana, Goa and Delhi. All types of schools— rural, urban, tribal, private, aided and government schools were selected for data collection. Results indicated that girls have a significantly higher interest in agriculture and food processing, hospitality, travel and tourism, creative and performing arts, textiles and fashion, education and training, beauty and wellness and security, defence and police, as compared to boys. Boys, on the other hand, showed higher preference for areas like ICT, science and technology and sports and athletics as compared to girls. The study suggests different strategies to orient students about various vocational opportunities which would develop decision-making skills.